Social differences in the sports behaviour of the Swiss population across time - Klostermann, Claudia; Lenze, Lars; Lamprecht, Markus; Nagel, Siegfried (Current Issues in Sport Science (CISS), 2023)
Changes in sports behaviour and activities over the last decades are often attributed to developments of individualisation and differentiation in society. Existing empirical studies confirm that sporting activity is increasingly differentiated, with the proportion of regular sport-active people growing, as well as access improving for those previously less well represented, for example, women and older people. However, more men than women and more younger than older people are active in sports clubs (Lamprecht et al., 2020). This lecture will consider the extent to which social differences and inequalities in sporting behaviour have decreased in the Swiss population over recent decades. The underlying processes of exit and entry, age, cohort, and period effects are also examined. Mayer’s life course approach (1990; 2009) is the theoretical and methodological framework for the investigation of change processes in contemporary history, where “social structures and their changes can be partially reconstructed from individual trajectories” (Mayer, 1990, p.8). Changes in modern sport can therefore be reconstructed through personal longitudinal data and its aggregation. In 2019, this study gathered the trajectories of sport and physical activities of a total of 1,456 people living in Switzerland aged 15 to 76 years using a retrospective telephone survey. For the time-historical analyses, age cohorts of those born 1943 to 1950, 1951 to 1960, through to those born 1981 to 1990 were constructed. Information on sporting activities over the life course from childhood to the present from the periods 1950s to 2010s was then chronologically classified. The analyses confirm existing research that shows older people practice sport activities in clubs less frequently. This negative age effect in club sport can be seen across all age cohorts and time periods (all p < .001). Binary logistic regression analyses also indicate that this age effect is most pronounced, with an OR of 0.35, in the youngest age cohort born 1981 to 1990, whereas in the oldest cohort born 1943 to 1950, shows OR = 0.67. In recent decades, more child and adolescent girls have gained access to club sport, with a decline in the gender difference from approximately 22 percentage points in the 1950s/1960s to approximately 6 percentage points in the 2000s/2010s. A positive age effect can be observed in self-organised sporting activities. This is more pronounced in the younger age cohorts, OR = 2.72, than in the older, OR = 1.77. These historical analyses demonstrate that age differences in organisational forms of sport remain, but that gender differences in club sport have been minimised, particularly in childhood and adolescence. In addition, the effects have tended to become greater in recent years and changes in the forms of organisation tend to become more significant over time. References Lamprecht, M., Bürgi, R. & Stamm, H. (2020). Sport Schweiz 2020. Sportaktivität und Sportinteresse der Schweizer Bevölkerung. Bundesamt für Sport BASPO. Mayer, K. U. (Ed.). (1990). Lebensverläufe und sozialer Wandel. Kölner Zeitschrift für Soziologie und Sozialpsychologie, 31[Special issue]. Mayer, K. U. (2009). New directions in life course research. Annual Review of Sociology, 35, 413–433. https://doi.org/10.1146/annurev.soc.34.040507.134619